Using possible intuitive virtual applications requested through metaverse nike advertising in shoes sales and a proposition study on the metaverse shoes sales application model - ALGÜL, NEVİN (My University, 2022)
The fact that the space has gained movement and dimension is obvious as the brands begin to design visual communication through the metaverse and other virtual applications in their advertisements. The effect of this movement and size on the customer; While designing visual communication, symbols, signs, letters, etc. belonging to the brand should be used. In the presentation of linguistic or visual indicators identified with the brand, such as the preference and the effect of this preference on the customer, the suggestions of what this trend, especially seen in sports shoes, can turn into in the future, and the energy of need that can be felt, which can be the source of the designs, will be the subject of research in another article, In this enjoyable, important issue that concerns all of us and where the excitement of the future takes place, the current online shoe sales trends are briefly mentioned and presented in the online shoe shopping of the customers; metaverse and beyond, where customers can choose the most suitable shoe for them, five senses plus intuition, trends An ideal shoe application model design that can be measured will be tried to be idealized and stylized. Since it is the first, it is a mystery to what extent it can be approached to the ideal. But the method applied to shoes designed for astronauts can be inspiring. As a social scientist, it is clear that further research is needed. However, this study is limited to hosting an amateur enthusiasm and will be limited to giving the idea and handing over the work to the expert. This article, which deals with the use of virtual universes for point-and-shoot solutions to the problems that people have experienced in daily life, is firstly based on an experiment on whether virtual universes can be used to change and improve the shoe industry. In other words, can they use the 3D technology they started to use in their advertisements to measure feet in the world and to produce smart shoes? These shoes will be so smart that you can continue to wear the same shoes with this feature with a small adjustment without having to take them off when your foot is sprained. From the area that is still new; Potential situations will be presented in the opinion and perhaps wishes section of the article by evaluating customer orientations in the feedback from the end user. In summary: This article will focus on three issues: How the language used in the field of shoe body language, which originates from the capitalist approach to the sale of shoes to the global market, can be negatively affected by the end consumers at the national level; It will be emphasized a little on those who may experience confusion. It will be designed that hitting the target in the field of shoes and clothing in the global market may not be difficult at all with the developed metaverse type and derivative applications. 3. The design of a metaverse sensor that will be able to measure the customer's foot in general socially and individually in a developed level, to perceive the five senses of the customer, to sense the unconscious tendency created by the intuition arising from his experience while the shoe is on his foot, and to put it into data will be made amateurishly. It can be considered as a thought exercise on the use of augmented reality in shoe wear, online and/or in the first prototype trials, data acquisition and presentation
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Metaverse; Metaversal Shoe Application; Augmented Reality in Online Shoe Sales; Metaversal Recycling; Five Senses; Sense.